Effect Of Siplo Induction Long And Dosage Of Rabbit Urine Poc On The Growth And Results Of Crumble Lettage (Lactuca sativa L.) - Nizar Nufikha Albafana; Sugiarto Sugiarto; Siti Muslikah (AGRONISMA, 2021)
Curly lettuce (Lactuca sativa L.) is a horticultural commodity that has good prospects and commercial value. Lettuce horticultural commodities have very high economic value. The lettuce plant was originally used as a medicinal ingredient and later known as a vegetable ingredient. Curly lettuce has benefits as raw vegetables, fresh vegetables for side dishes at parties to be used as fresh vegetables and also serves as a medicine for internal heat and facilitate digestion (Zailani, Kuswardani, Panggabean, 2019). The design used in this study was a factorial Randomized Block Design (RAK) with 3 treatments for each control, 5 samples and 3 replications, 3 controls and treatments randomized by lot. Factor 1 is SIPLO induction I1 = 45 minutes, I2 = 60 minutes, I3 = 75 minutes Control = No treatment. Factor 2 dose of POC rabbit urine U1 = 50 ml/liter, U2 = 100 ml/liter, U3 = 150 ml/liter. This study observed several growth variables such as plant height, leaf area, and number of leaves. Based on further testing, 5% BNJ on growth parameters showed that the I1U2 treatment (induction of Siplo 60 min/plot and rabbit urine dose of 50 ml/plot) showed significantly different results from the control. while on the quantity and quality variables, in general the I1U1 treatment showed the highest results and was more different from the control